PERSEPSI MASYARAKAT TERHADAP PENGELOLAAN TAMAN WISATA ALAM TELAGA WARNA KABUPATEN BOGOR, PROVINSI JAWA BARAT - Suherlan, Elka Pebriyandi; Salampessy, Messalina L.; Rusli, Abdul Rahman (Jurnal Nusa Sylva, 2021)
The existency of conservation areas and surrounding communities is an inseparable part. The interaction of the people with the forest area is influenced by the perception of local community surrounding the forest. This study was aimed to describe the community's knowledge about the Nature Tourism Park (NTP) and community perceptions of the management of NTP. This research was conducted in May - June 2020 in Tugu Utara Village, Cisarua District, Bogor. Data obtained through field observations, interviews, questionnaires and literature studies, and were analyzed quantitatively by describing the percentage of people's understanding of the management of NTP. The results show that the community has high knowledge of the NTP concept, function and role of NTP, NTP management and community participation in NTP management and the community has a good level of understanding about the existence and role and function of NTP for the community, a good understanding of the active role of the community. in the management of TWA and the importance of building cooperation in the management of NTP. Therefore, it is necessary to make efforts to increase the role and participation of the local community in the effort to utilize the potential of the area and its preservation.